BIOMASS GASIFICATION IN CIRCULATING FLUIDIZED BED FOR POWER PRODUCTION - Χριστοδούλου, Χρήστος (Σχολή Μηχανολόγων Μηχανικών, 2015)
Current society needs for fuel and chemical commodities are strongly dependent on fossil resources. This dependence can lead to economic instabilities, political problems and insecurity of supplies. Moreover, a dramatic “collateral damage” that endangers the future of the planet is global warming, which is associated with the massive use of fossil resources. 0Nowadays, biomass is the only renewable source, able to obtain various liquid, gaseous, solid products, and electricity. This is owed to the fact that biomass consists of organic compounds. Furthermore, the contribution of biomass’products is considered CO2 neutral and thus generate CO2 credits. The thermochemical processing of biomass contributes to the challenge of reduced use of fossil resources by producing electricity or liquids feedstock able to lessen the “fossil dependence”. A promising process is that of biomass gasification. The aim of this thermochemical process is to product a mixture of gases (synthesis gas) rich in CO, H2, CH4, CO2 and H2O. This technology can provide both syngas for advanced syntheses but also to run boiler and power producing. Due to many drawbacks of biomass gasification, this process is not yet commercial. Some issues which seem quite interesting for the scientific community are related to the increase of the ash melting point. The melt of the inorganic constituents of ash leads to agglomerates with bed material particles. As a result of this phenomenon is the defluidization (when the process takes part in fluidized bed reactors). Another important disadvantage is the high concentration of tars in the product gas. The reduction of tars’ levels is a challenge. In this dissertation, the exploitation of biomass for power production via air gasification in an atmospheric circulating fluidized bed reactor is investigated. The goal is the tar reduction in the syngas, and the research for the tendency of agglomeration formation for different biomass species. During this PhD thesis several experimental campaigns were conducted for sunflower and jatropha cakes, willow and cardoon. The influence of the operating temperature and the bed material on syngas quality was investigated. Within the borders of an advanced zero - waste – biorefinery operation, for which the gasification unit constitutes a basic element, the aforementioned seeds residues were studied after the oil was extracted. The sunflower and jatropha energy crops thrive – with very satisfactory efficiency – in the Mediterranean area. There was defluidization phenomenon only during cardoon gasification using olivine as bed material. The defluidization temperature was low. Attempts for tackling this problem were conducted by means of using a blending of cardoon and giant reed. The results of this trial were encouraging since there was no loss of fluidization. Two cardoon gasification trials were contacted with two different inert materials. Both the first time with olivine and the second with magnesite, a problem due to defluidization was presented. The experimental trial with magnesite as inert material took place in the Delft University unit. This particular experimental facility is an atmospheric circulating fluidized v bed reactor. The trial was performed using oxygen and steam as oxidizing medium. After two hours of experimental procedure in a temperature of 750oC a loss of fluidity was noted. As it was mentioned above, this particular defluidization problem was confronted by carrying our gasification trials with a mixture of cardoon – giant reed. Giant reed was chosen because it a biomass species with properties similar to cardoon. The trial was performed in the CERTH experimental unit, with olivine as inert material. The operation temperature reached 800oC and during the entire experiment no agglomeration related problem occurred. All fuels were tested using three different bed materials. The bed materials were silica sand, olivine (fresh) and calcined olivine. Results derived from experimental tests show that calcined olivine has catalytic properties on tar reduction. All the experimental trials took place in an atmospheric fluidized circulating bed reactor. During them, the effect of temperature and inert material on the quality of syngas produced was investigated. Despite the fact that air - gasification process is autothermal, the reactor temperature was controlled with help from external resistances that provided the necessary heat. The entire experimental series was carried out in two different temperatures, 750oC and 800oC. The quality of the produced syngas for every fuel had great similarities with the gas that came from willow gasification. An important difference was presented only in the produced hydrogen concentration, which in the case of sunflower and jatropha residues was till three times higher than the corresponding percentage noted during willow gasification. Although it was the first time that gasification trial in a fluidized bed with those two residues and cardoon were performed, the results were quite encouraging. Consequently, these species can be considered as promising fuels for industrial scale applications. Every fuel was tested with three different bed materials, in order to thoroughly investigate their effect in tar concentration. These materials were silica sand, olivine and calcined olivine. The results derived from the trials showed that calcined olivine has good catalytic properties as far as tar reduction is concerned. In particular, a reduction up to 80% in the produced tars concentration was observed in comparison with the experiments carried out with silica sand in the case of sunflower residues. After the completion of the trials, speciments from three different places of the reactor were collected: the lower part of the riser, the L – valve and the lower part of the second cyclone. Subsequently, a series of analyses was performed for the characterization of these speciments. All these analyses led to the extraction of important conclusions for the bed materials. A quite interesting observation was that the cracks present in the internal structure of olivine, aid – amplify the penetration of the particles from inorganic ash elements, mainly calcium and potassium. This phenomenon is considerably more intense when olivine is thermally processed in a furnace (calcination). During calcination the size of the cracks increases and as a result the penetration of the inorganics is enduced. The presence of inorganics inside the particles reduces greatly the possibility of defluidization due to ash melting. This conjecture is supported by the fact that defluidization never occurred during all of the experiments with olivine or calcined olivine. Unfortunately though, the increase of the crack size reduces the mechanical durability of the calcined olivine particles. This was ascertained by conducting resistance trials on the inert materal particles against mechanical wear